Uso de funções de pedotranferência entre atributos físicos de solos sob plantio direto - Marcolin, Clovis Dalri (2009)
Good physical quality of agricultural soils is essential to plant growth and environmental conservation. And there has been a constant attempt to assess physical soil properties or indicators that can quantify such quality. The aim of the present study was to evaluate the physical quality of soils under no tillage and to develop pedotransfer functions that allow describing the physical quality of these soils in the A horizon. Disturbed and undisturbed samples were collected from 10 soils in the State of Rio Grande do Sul, Southern Brazil, at six depths (from 5 cm to 30 cm). All the soils analyzed have been managed under no tillage for over 10 years. Granulometry, organic matter, soil density, maximum bulk density, relative density, soil resistance to penetration, least limiting water range and S index were determined. Results show that the adjustment of maximum bulk density according to clay and organic matter contents is appropriate